SPE Annual Technical Conference and Exhibition 1992
DOI: 10.2118/24930-ms
|View full text |Cite
|
Sign up to set email alerts
|

Early Performance and Evaluation of the Kuparuk Hydrocarbon Miscible Flood

Abstract: SPE Members Abstract A small-scale hydrocarbon miscible flood was initiated at the Kuparuk River Unit on the North Slope of Alaska in mid-1988, three years after the start-up of waterflooding. This Small Scale EOR (SSEOR) project, along with an infill drilling program, is improving recovery from a stratified and highly faulted sandstone reservoir. The project design was aided by limited compositional reservoir simulation. The design calls fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The SSEOR project injection rate has averaged 34 MMScf/d (1 million Sm3/d). Further details about the project are reported by Reinbold et al (1992).…”
Section: Mwag Field Performancementioning
confidence: 99%
“…The SSEOR project injection rate has averaged 34 MMScf/d (1 million Sm3/d). Further details about the project are reported by Reinbold et al (1992).…”
Section: Mwag Field Performancementioning
confidence: 99%
“…A single-well tracer test indicated that the S orw after many PV's is approximately 27"3%. 9 The tracer-test results were dominated by a thief zone. These two independent values of S orw are reasonable estimates for S orw in a few of the subunits of the C-sand at field conditions, which range from low to high throughput.…”
mentioning
confidence: 99%
“…An extensive fieldwide refracturing program was initiated in 1988 to increase withdrawal from the less prolific A-sand. 7,8 An EOR pilot was initiated in 1988 on two drillsites, 9,10 and subsequently expanded to one of the IWAG drillsites in 1993 to test the MWAG after IWAG process. Largescale expansion of EOR at Kuparuk is in progress.…”
mentioning
confidence: 99%
See 2 more Smart Citations